Evaluating Immediate Feedback via Bug-in-Ear as an Evidence-Based Practice for Professional Development. Issue 4 (December 2018) - Schaefer, John M.; Ottley, Jennifer R.
Observation and performance feedback to support traditional training methods are central tools for preservice practitioner preparation and in-service practitioner professional development. Research highlights how some specific characteristics of feedback (e.g., the latency between behavior and feedback) can impact the effectiveness. One method of enhancing the effects of feedback may be immediate feedback delivered through bug-in-ear technology. This review identified 17 intervention studies that examined the use of immediate feedback via bug-in-ear with preservice and in-service practitioners. We evaluated these studies using What Works Clearinghouse quality standards and determined that immediate feedback with bug-in-ear technology has a strong evidence base for increasing frequency and accuracy of teaching behaviors of practitioners in a variety of classroom settings. This review discusses findings on that evidence base as well as findings on feasibility and acceptability of this intervention. We also discuss limitations of current research and potential directions for future research on this method.